Development of Present Indian Insurance Industry: The Role of Life Insurance in Mitigating Financial Uncertainty (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Life insurance  is  universally acknowledged  to  be an  institution  which eliminates ‘risk.’ Substitutingcertainty for uncertainty and comes to the timely aid of the family in theunfortunate event of death of the breadwinner. By and large, Life insurance iscivilization’s partial solution to the problems caused by death. Life insurance,in short, is concerned with two hazards that stand across the life – path ofevery person that of dying prematurely leaving a dependent family to send oritself and that of living old age without visible means of support.